Sustaining the Workforce: A JD-R Perspective on Mitigating Dual Role Stress and Enhancing Job Satisfaction in Hospitals - Kaslam, Surawijaya Bakhtiar; Isa, Muzakar; Praswati, Aflit Nuryulia (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This narrative review synthesizes studies from 2017-2025 examining the effects of double job roles and work stress on hospital employee performance, emphasizing burnout and job satisfaction as mediators.Methodology: Guided by the Job Demands-Resources (JD-R) model, this review utilized Scopus, PubMed, ScienceDirect, and Google Scholar, selecting 46 studies (21 representative exemplars) published between 2017 and 2025. The review adopted a narrative design enriched with systematic synthesis elements, following an adapted PRISMA framework for thematic coding and analysis.Results: Double job assignments and work stress consistently emerged as high-strain job demands, leading to role overload and emotional exhaustion. Burnout functions as the primary psychological conduit, translating stress and overload into performance decline and increased medical errors. Conversely, job satisfaction acts as a critical buffer, enhancing resilience, lowering turnover intention, and sustaining motivation. Organizational supports, such as effective leadership and adequate staffing, moderate these negative effects.Applications/Originality/Value: The findings provide critical insights for hospital administrators and health ministries for workforce planning, performance management, and well-being initiatives. The synthesis contributes to the theoretical refinement of the JD-R framework within healthcare contexts, integrating socio-structural variables.